Graduation outcomes of international undergraduates whose enrollment history coincided with the Coronavirus pandemic - Fass-Holmes, Barry (Journal of International Students, 2026)
What were the graduation outcomes of the international undergraduates enrolled at an American West Coast public university throughout the coronavirus pandemic (COVID-19)? The present exploratory study compared the university’s international undergraduates entering in fall 2019 (FA19; pandemic cohort) with counterparts entering in fall 2013 (FA13; prepandemic baseline); the FA13 cohort was the final cohort whose undergraduate enrollment completed before COVID-19’s spring 2020 onset. FA19 transfers’ cumulative two-year graduation rate was significantly better and their times to degree were somewhat better than FA13 counterparts’ (76.2% vs. 61.6%; 2.2 vs. 2.4 academic years). FA19 first-time undergraduates’ cumulative six-year rates were similar to and times to degree significantly better than FA13 counterparts’ (69.5% vs. 71.7%; 4.3 vs. 4.8). These findings suggest that this university’s FA19 cohort unexpectedly had mostly better graduation outcomes than the FA13 baseline despite the disruptions coinciding with COVID-19. Implications for the research literature’s generalizations about international undergraduates are discussed.